Comparison of maxillary anterior teeth crown ratio (width/length) between gender in Laotian population - Phonepaseuth Sitthiphan (2018)
© 2015 Japan Health Sciences University & Japan International Cultural Exchange Foundation. Aim: To determine the distribution of facial types and to compare the crown width/length ratio of six maxillary anterior teeth between male and female in Laotian population. Materials and Methods: 100 male and 100 female, aged 18 to 35 years old, were recruited for the study. The facial measurements included the facial width, facial height and facial index. Classification of facial type either as the broad, average or narrow was performed according to the facial index. Crown width and length of maxillary anterior teeth were measured in millimeters from study models. The crown width/length ratio of maxillary anterior teeth were calculated. The frequency and percentage of each facial type was calculated. Independent t-test was used to assess the differences in the mean crown width/length ratio of each tooth type between male and female subjects. Error of measurements and the power of test were also determined. Result: In male group, there were 94 broad, 6 average and no narrow facial types. In female, there were 93 broad, 5 average and 2 narrow facial types. For broad facial type, in male group, the mean crown width/ length ratio of central incisor, lateral incisor and canine were 0.902 ± 0.098, 0.820 ± 0.097 and 0.871 ± 0.096 respectively. Similarly in female group, it was 0.944 ± 0.101, 0.876 ± 0.100 and 0.902 ± 0.098. Significant difference was found for the crown width/length ratio of central incisor, lateral incisor and canine between male and female with broad facial type (P < 0.05). Conclusion: Majority of Laotian subjects exhibited broad facial types. Differences in crown width/length ratio maxillary anterior teeth between gender could be used to design esthetic smile for Laotian population.